The South Pacific Islands Resist Diabetes With Intense Training (SPIRIT) Study : investigation of obesity markers and morphological, functional and genetic changes in the skeletal muscle : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Health Sciences, Institute of Food, Nutrition and Human Health, College of Health, Massey University at Wellington, New Zealand - Hayat, Irum (Massey University, 2013)
The skeletal muscle (SM), the major tissue for disposal of excess blood glucose, plays a big role in development of insulin resistance leading to type 2 diabetes mellitus (T2DM). Lipid accumulation and decline in mitochondrial activity in SM has been observed in people with T2DM. Several studies have demonstrated that exercise has the ability to increase SM lipid oxidation and mitochondrial activity and hence is effective as a treatment strategy for people with T2DM for improving blood glucose control and insulin sensitivity. The SPIRIT study was the first clinical randomised exercise trial involving a cohort of Polynesian New Zealanders with T2DM. The uniqueness of this study is that it is the first clinical trial in Polynesian population with grade 3 obesity (n=18; BMI 43.8 ± 9.5 kg/m2) and T2DM. The SPIRIT cohort underwent 16 weeks of progressive resistance training (PRT) or aerobic exercise (AER) training. The cohort showed no changes in HbA1c levels after 16 weeks of exercise and hence no improvement in their blood glucose control. This was an unexpected result and led to the following hypothesis which underlines this PhD study – "In skeletal muscle of SPIRIT cohort, metabolic adaptation to exercise is delayed due to metabolic inflexibility". To investigate this hypothesis, mitochondrial function and morphology, lipid droplet content and changes in gene expression pre and post exercise intervention were examined in the SM. Since the SPIRIT cohort showed no changes in weight, waist circumference and BMI, examination of the concentration of specific obesity markers pre and post exercise training also occurred. Mitochondrial function was examined pre and post 16 weeks exercise intervention by measuring the SM activity of three key mitochondrial enzymes; citrate synthase (CS) involved in Krebs cycle, beta-hydrxoyacyl-CoA dehydrogenase (BHAD) involved in fat oxidation and cytochrome c oxidase (COX) involved in electron transport chain. The PRT cohort showed statistically significant increases in activity for COX (P=0.005) and CS (P=0.007) with very large effect size (2.3 ± 1.3 and 1.8 ± 1.3 respectively). AER exercise led to significant increases in the activity for all three enzymes COX (P=0.01), CS (P=0.03), BHAD (P=0.03) with moderate effect size for both COX and CS activity but very large effect for BHAD (6.7 ± 1.2). For all three enzymes there were statistically significant differences (P<0.05) between the AER and PRT groups. These results demonstrate increased mitochondrial activity and functioning after 16 weeks of PRT or AER exercise.
Keywords: Non-insulin-dependent diabetes; Morbid obesity; Exercise therapy; Physiology; musculoskeletal system; Polynesians; Pacific people; Pasifika; Maori; Health and hygiene; New Zealand